Sosialisasi Diversifikasi dan Strategi Promosi Berbasis E-Marketing dalam Meningkatkan Penjualan Produk Anyaman dari Daun Pandan - Tholib Hariono; Hilyah Ashoumi; Ardiansyah Ardiansyah; Muhammad Mubarok Jauhari; Nur Adinda Rahmasari; Nabila Nur Tania; Binti Ayu Fadhilah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2025)
The rapid development of information technology in the globalization era has impacted various aspects of life, including business. In the context of marketing, e-marketing has become essential to expanding market reach and increasing product competitiveness. In Asem Gede Village, pandan leaf weavers—mostly women—face limitations in marketing their products widely. Currently, their pandan leaf crafts are only sold through middlemen and traditional markets, resulting in limited income. This socialization and training program aims to provide an understanding of product diversification and digital marketing strategies, with the goal of increasing the income of these weavers. The results of this activity show a significant increase in participants' understanding of product management and the use of e-marketing strategies. Before the training, many participants were unfamiliar with e-marketing concepts. However, after the socialization, their interest and readiness to adopt digital promotion strategies increased dramatically. Products that were previously limited to mats have now expanded to include bags, tissue boxes, and other high-value items. This socialization has positively impacted the local economy and empowered the community, especially women, by increasing income and preserving traditional skills.